PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KINERJA PNS DI BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN DAERAH KOTA KEDIRI - Riana Dwi Ambarwati; Imam Baehaqi (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This study aims to identify and analyze the effect of the training program and carier development as independent variables either partially or simultaneously on employee performance in BKPPD of Kediri as the dependent variable. Methods this study used a questionnaire with 50 employee in BKPPD of Kediri as the sample. To determine the effect of the training program and carier development to employee performance used multiple linear regression statistical techniques and fatherly significance testing using the F test and t test using SPSS. The results of this study concluded that the partial of the two independent variables, only the training programs that have a significant influence on employee performance. No significant effect of the carier development, but the two independent variables simultaneously have a significant influence on variable employee performance.